2008
DOI: 10.1093/geronb/63.6.s337
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Exposure to Poor Nutrition and Infectious Diseases and Its Effects on the Health of Older Puerto Rican Adults

Abstract: Objectives We examined the effects of early life exposure to poor nutrition and infectious diseases on adult heart disease and diabetes using season of birth as an indicator to help disentangle the effects on health of early life exposure from effects associated with other childhood conditions. Methods Using data from 60- to 74-year-old Puerto Ricans who lived in rural areas during childhood (n = 1,457), we estimated the effects of seasonal exposure during late gestation on the probability of diabetes and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…Island-residing Puerto Ricans in the early 20th century experienced similar life circumstances and demographic forces as those in other developing Latin American countries, including overpopulation and lower levels of economic development. In addition, the population was predominantly living in rural areas where residents were more likely to be malnourished and exposed to infectious diseases (McEniry, 2014), conditions that have been linked to worse health in late life (Crimmins & Finch, 2006; McEniry & Palloni, 2010; McEniry, Palloni, Dávila, & García, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Island-residing Puerto Ricans in the early 20th century experienced similar life circumstances and demographic forces as those in other developing Latin American countries, including overpopulation and lower levels of economic development. In addition, the population was predominantly living in rural areas where residents were more likely to be malnourished and exposed to infectious diseases (McEniry, 2014), conditions that have been linked to worse health in late life (Crimmins & Finch, 2006; McEniry & Palloni, 2010; McEniry, Palloni, Dávila, & García, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Along with still growing evidences coming from the studies carried out worldwide that continually confirm the importance of classical CVD risk factors, the knowledge of the relationship between disease risk and poverty has expanded only recently (Koch, 2011;Kolarcik et al, 2009;McEniry et al, 2008;Spiroski et al, 2011).…”
mentioning
confidence: 99%
“…In previous work (McEniry et al, 2008; McEniry & Palloni, 2010), we showed a strong association between season of birth and adult heart disease and diabetes among older Puerto Ricans who lived in the countryside during childhood, suggesting the importance of the timing of adverse early life exposures for older adult health. In this article, we use season of birth but also infant mortality rates (IMR) to further examine the strength of these effects.…”
Section: Introductionmentioning
confidence: 63%
“…However, season of birth has been shown to be a good proxy for very early life conditions in utero and early infancy that precipitates poor adult health in the developed world. Being born at the end of the harvest season has been associated with better adult health (Doblhammer, 2004; Costa, 2005; Gavrilov & Gavrilova, 2005; Moore et al, 1999; Muñoz-Tuduri & García-Moro, 2008; McEniry et al, 2008; McEniry & Palloni, 2010, Mazumder et al, 2009). These results have been attributed to the importance of the timing of nutritional insults during late gestation (Doblhammer, 2004) which provides support for interpretations such as the Barker (1998) hypothesis.…”
Section: Introductionmentioning
confidence: 99%